PENGARUH BEBAN KERJA TERHADAP TURNOVER INTENTION DENGAN PERCEIVED ORGANIZATIONAL SUPPORT (POS) DAN CONTINUANCE COMMITMENT SEBAGAI VARIABEL MODERASI: Analyzing Workload, Perceived Organizational Support, and Commitment at Baitul Maal wat Tamwil (BMT) - Khoirunisa, Laila; Zakiy, Muhammad; Jadmiko, Purbo; Samsuddin, Ardian (Institut Agama Islam Negeri Ponorogo, 2025)
Human resources are an important aspect of an organization that cannot be separated from turnover problems. The high turnover rate remains a serious problem that organizations must minimize. One of the factors that can cause high turnover rates is the employee workload. Despite this, some factors can be highlighted to reduce turnover rates due to high workload, namely, perceived organizational support (POS) and continuance commitment. This study aimed to determine the effect of workload on turnover intention, with perceived organizational support (POS) and continuance commitment as moderating variables. This study used a quantitative method. Data were collected using questionnaires distributed to employees of BMT BIF Yogyakarta. The research respondents were 75 people collected using a saturated sampling method. Data analysis in this study used Structural Equation Modeling (SEM) in the Smart PLS 3.2.9 application. The results of the study show that there is an influence between workload and turnover intention. In addition, the perceived organizational support variable can also moderate the effect of workload on turnover intention, while continuance commitment cannot moderate the effect of workload on turnover intention. The managerial implications lead to the organization's role to always pay attention to the workload assigned to employees and to increase the perceived organizational support for employees so that turnover intention can be minimized.